2017
DOI: 10.1038/ncb3570
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow adipocytes promote the regeneration of stem cells and haematopoiesis by secreting SCF

Abstract: Endothelial cells and Leptin Receptor+ (LepR+) stromal cells are critical sources of haematopoietic stem cell (HSC) niche factors, including Stem Cell Factor (SCF), in bone marrow. After irradiation or chemotherapy, these cells are depleted while adipocytes become abundant. We discovered that bone marrow adipocytes synthesize SCF. They arise from Adipoq-Cre/ER+ progenitors, which represent ~5% of LepR+ cells, and proliferate after irradiation. Scf deletion using Adipoq-Cre/ER inhibited hematopoietic regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
422
1
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 390 publications
(455 citation statements)
references
References 66 publications
(79 reference statements)
14
422
1
6
Order By: Relevance
“…Zhou and colleagues revealed that adipocyte derived-stem cell factor is important for hematopoiesis (19). Stem cell factor is expressed by a number of bone marrow cell types as several other cytokines that bind to receptors on hematopoietic stem cells.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
See 3 more Smart Citations
“…Zhou and colleagues revealed that adipocyte derived-stem cell factor is important for hematopoiesis (19). Stem cell factor is expressed by a number of bone marrow cell types as several other cytokines that bind to receptors on hematopoietic stem cells.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
“…This growing evidence highlight the need for further investigation of the adipocyte derived signals involved in the bone marrow fat tissue influence on leukemia cell survival, progression, and spread. While Zhou and colleagues reveal that adipocyte-derived stem cell factor is an essential factor for hematopoietic stem cell regulation (19), its role in the modulation of tumor burden still needs to be explored. The mechanistic understanding of leukemic stem cells protection, through modulation of local concentrations of chemotherapy, support of tumor cells in a dormant state, or stimulation of overt anti-apoptotic signaling cascades is essential to the development of novel therapeutic strategies to blunt residual disease.…”
Section: Perspectives / Future Directionsmentioning
confidence: 99%
See 2 more Smart Citations
“…Adipocytes have also been investigated for their role in hematopoiesis, although their role is unclear at this time. 7,8 The adaptive potential of these cellular microenvironments to respond to both pathological and physiological changes highlights the complex and vital interactions of the cellular constituents of the niche as well the important differences between homeostasis and postablated marrow niches. Successful hematopoietic reconstitution of donor HSC after HCT is dependent on a number of intricate cellular interactions, including recovery of the sinusoidal endothelium, 1,9-11 migration of megakaryocytes to the endosteal space, and osteoblast proliferation.…”
Section: Introductionmentioning
confidence: 99%